THE IMPLEMENTATION OF POSTERS AS LEARNING MEDIA IN ENGLISH FOR YOUNG LEARNERS CLASSROOM - Maula, Regina Cahyatul; Gumiandari, Septi (Sindoro: Cendikia Pendidikan, 2025)
Learning that involves visualisation through posters can provide a more interesting and enjoyable learning experience for students, thus motivating them to be more active in the learning process. This study aims to explore young students' experiences and perceptions of using posters as a medium in teaching English vocabulary. This research uses qualitative method with case study approach. The research subjects were 20 grade 4 students in an elementary school in Cirebon city who were involved in English vocabulary learning activities using posters. The research data were collected through observation, interviews, and documents. The data obtained were analysed using thematic analysis technique. This study provides implications for English teachers, especially those who teach in primary schools, to integrate posters as an effective and interesting medium in teaching English vocabulary to primary school students.